2018
DOI: 10.7554/elife.37082
|View full text |Cite
|
Sign up to set email alerts
|

The plant pathogen Pseudomonas aeruginosa triggers a DELLA-dependent seed germination arrest in Arabidopsis

Abstract: To anticipate potential seedling damage, plants block seed germination under unfavorable conditions. Previous studies investigated how seed germination is controlled in response to abiotic stresses through gibberellic and abscisic acid signaling. However, little is known about whether seeds respond to rhizosphere bacterial pathogens. We found that Arabidopsis seed germination is blocked in the vicinity of the plant pathogen Pseudomonas aeruginosa. We identified L-2-amino-4-methoxy-trans-3-butenoic acid (AMB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 80 publications
(121 reference statements)
0
34
0
Order By: Relevance
“…In the presence of GA, the GA receptors GA INSENSITIVE DWARF1 ([GID1]a, GID1b, and GID1c) and the F-box ubiquitin ligase SLEEPY1 (as an SCF SLEEPY1 complex) recruit DELLA proteins for ubiquitination and subsequent degradation (Dill et al, 2004;Ueguchi-Tanaka et al, 2005;Nakajima et al, 2006;Harberd et al, 2009;Claeys et al, 2014). RGL2 is a critical suppressor of seed germination (Lee et al, 2002;Tyler et al, 2004;Piskurewicz et al, 2008), and GAI and RGA also repress seed germination (Cao et al, 2005;Piskurewicz et al, 2009;Chahtane et al, 2018). All five DELLA genes are expressed during seed germination (Tyler et al, 2004), and GAI, RGA, and RGL2 are responsive to ABA during seed germination (Piskurewicz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of GA, the GA receptors GA INSENSITIVE DWARF1 ([GID1]a, GID1b, and GID1c) and the F-box ubiquitin ligase SLEEPY1 (as an SCF SLEEPY1 complex) recruit DELLA proteins for ubiquitination and subsequent degradation (Dill et al, 2004;Ueguchi-Tanaka et al, 2005;Nakajima et al, 2006;Harberd et al, 2009;Claeys et al, 2014). RGL2 is a critical suppressor of seed germination (Lee et al, 2002;Tyler et al, 2004;Piskurewicz et al, 2008), and GAI and RGA also repress seed germination (Cao et al, 2005;Piskurewicz et al, 2009;Chahtane et al, 2018). All five DELLA genes are expressed during seed germination (Tyler et al, 2004), and GAI, RGA, and RGL2 are responsive to ABA during seed germination (Piskurewicz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, GA was abundant in foxtail millet after infection with S. graminicola, signal transduction pathways were suppressed, and the expression of the phytochrome-interacting factor TF3 was significantly reduced. Chahtane et al (2018) [25] reported that l-2-amino-4-methoxy-trans-3-butenoic acid secreted by Pseudomonas aeruginosa directly acts on…”
Section: Discussionmentioning
confidence: 99%
“…In our study, GA was abundant in foxtail millet after infection with S. graminicola, signal transduction pathways were suppressed, and the expression of the phytochrome-interacting factor TF3 was significantly reduced. Chahtane et al (2018) [25] reported that l-2-amino-4-methoxy-trans-3-butenoic acid secreted by Pseudomonas aeruginosa directly acts on DELLA proteins of the GA signal transduction pathway to inhibit seed germination in Arabidopsis thaliana, regardless of GA content. Our results suggest that S. graminicola infection might block the GA signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it is clear that seeds have developed a sentinel molecular system to ensure that germination progresses to plantlet growth in supportive biotic and abiotic environments. Notably, and in contrast to their interaction with P. fluorescens , Arabidopsis seeds block their germination in the presence of the plant pathogen Pseudomonas aeruginosa to prevent potential damage the bacterial cells could inflict on the emerging plantlet (Chahtane et al ., 2018). This response is based on detection of molecules secreted by pathogenic bacteria into the spermosphere, such as l ‐2‐amino‐4‐methoxy‐trans‐3‐butenoic acid (AMB), a member of the oxyvinylglycin family, whose biological functions remain poorly understood.…”
Section: Initial Contact: Microbe–seed Interactionsmentioning
confidence: 99%